Analysis and assessment of conventional and platform-based mining methods adopted at the UNACEM S. A. A. company limestone quarry - Gutiérrez Arroyo, Kenning Georking (2020)
This research aims to provide a statistical and geostatistical analysis and assessment of a limestone quarry using Studio RM Datamine software. Unit costs of conventional and platform-based mining methods will lead to the selection of the method that optimizes the extraction of limestone, the Bieniawski geomechanical classification (1989), rock mass rating (RMR), and slope stability factor of safety; all of which are indexes to assess fall rock risk. The objective of this research is based on rock mass characterization, design parameters estimation and cost quantification of the explosives of both mining methods, which will allow a safe and sustainable operation over time.